2009
DOI: 10.1152/ajpheart.00432.2009
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin is a major vasoconstrictor involved in hindlimb vascular responses to stimulation of adenosine A1 receptors in the nucleus of the solitary tract

Abstract: Our previous study showed that stimulation of adenosine A1 receptors located in the nucleus of the solitary tract (NTS) exerts counteracting effects on the iliac vascular bed: activation of the adrenal medulla and ␤-adrenergic vasodilation versus vasoconstriction mediated by neural and unknown humoral factors. In the present study we investigated the relative contribution of three major potential humoral vasoconstrictors: vasopressin, angiotensin II, and norepinephrine in this response. In urethane-chloralose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 44 publications
(163 reference statements)
4
19
0
Order By: Relevance
“…For instance, in cat, stimulation of the HDA elicits monosynaptic excitatory [11] and inhibitory [10] postsynaptic potentials in NTS neurons that receive inputs from baroreceptors. Thirdly, HDA stimulation elicits rapid adenosine release in the NTS derived from extracellular ATP [20], presumably eliciting a β-adrenergic iliac vasodilation that is overridden by a vasopressinergic vasoconstriction [41,42]. Nonetheless, subunits of P2 receptors are expressed in NTS neurons of rat [14,15]; and the reductions in HVC responses seen here can be explained by blockade of input signals from the HDA to the NTS [7,8], independent of the pathways in control of AP and HR increases.…”
Section: Hindlimb Vasodilation In Alerting-defense Responses Is Mediamentioning
confidence: 72%
“…For instance, in cat, stimulation of the HDA elicits monosynaptic excitatory [11] and inhibitory [10] postsynaptic potentials in NTS neurons that receive inputs from baroreceptors. Thirdly, HDA stimulation elicits rapid adenosine release in the NTS derived from extracellular ATP [20], presumably eliciting a β-adrenergic iliac vasodilation that is overridden by a vasopressinergic vasoconstriction [41,42]. Nonetheless, subunits of P2 receptors are expressed in NTS neurons of rat [14,15]; and the reductions in HVC responses seen here can be explained by blockade of input signals from the HDA to the NTS [7,8], independent of the pathways in control of AP and HR increases.…”
Section: Hindlimb Vasodilation In Alerting-defense Responses Is Mediamentioning
confidence: 72%
“…The relative contribution of three neural and humoral vasoactive factors (sympathetic and vasopressinergic vasoconstriction opposed by ␤-adrenergic vasodilation) to the regional vascular responses evoked by selective stimulation of NTS A 1 adenosine receptors was studied in 53 male Sprague-Dawley rats. Our previous studies showed that only these three vasoactive factors significantly contributed to iliac vascular responses evoked by stimulation of NTS A 1 adenosine receptors (25). The relative changes in iliac (IVC), mesenteric (MVC), and renal (RVC) vascular conductance evoked by microinjections into the NTS by the selective A 1 adenosine receptor agonist CPA (Tocris) observed in intact animals (n ϭ 8) were compared with the responses evoked after the following six experimental procedures: protocol 1, bilateral adrenalectomy (ADX, n ϭ 8); protocol 2, blockade of ␤-adrenergic receptors (n ϭ 7); protocol 3, selective vasopressin V1 receptor blockade (VX, n ϭ 7); protocol 4, sinoaortic denervation (SAD, n ϭ 7); protocol 5, bilateral adrenalectomy combined with selective vasopressin V1 receptor blockade (ADX ϩ VX, n ϭ 8); and protocol 6, sinoaortic denervation combined with bilateral adrenalectomy (SAD ϩ ADX, n ϭ 8).…”
Section: Methodsmentioning
confidence: 99%
“…All procedures were described in detail previously (2,21,24,25,32,(37)(38)(39). Briefly, male SpragueDawley rats (350 -400 g; Charles River) were anesthetized with a mixture of ␣-chloralose (80 mg/kg) and urethane (500 mg/kg) intraperitoneally, tracheotomized, connected to a small animal respirator (SAR-830; CWE, Ardmore, PA), and artificially ventilated with a 40% oxygen-60% nitrogen mixture.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations